The impact of irrigation conditions on the spatial development of microbial colonies in bioheaps - Chiume, Rebecca Angela (Centre for Bioprocess Engineering Research, 2014)
This thesis contributes to the bioleaching knowledge base by improved understanding of the relationships between hydrodynamics and micro-organism-ore contacting and colonisation through an integrated study of microbiological and hydrological aspects of heap bioleaching within systems that mimic actual bio-heap environments.